Helicobacter pylori eradication and associated factors: dual therapy versus standard triple therapy in Lima, Peru - Ruiz-Cortez, Renatto (2025)
Objective: Helicobacter pylori (H. pylori) infection is the most important risk factor for gastric cancer development. Dual therapy can achieve higher eradication rates than standard triple therapy, and the factors associated with lower eradication rates have not been fully studied. The objective of our study was to evaluate the H. pylori eradication rate and its associated factors using dual therapy versus standard triple therapy. Materials and methods: This retrospective cohort study included 1,506 patients with H. pylori infection who received dual therapy or standard triple therapy. Eradication was confirmed with urea breath test. Chi-square (χ) test was used to analyze categorical variables, and relative risk (RR) was used to assess associations between eradication rates and clinical variables. Results: Eradication was higher with dual therapy, with 84.58% (384/454) versus 73.86% (777/1052) with standard triple therapy (p<0.001). The overall eradication rate with esomeprazole was 82.13% (648/789), followed by lansoprazole at 73.70% (213/289) and pantoprazole at 70.09% (300/428) (p<0.001). No significant differences were found regarding comorbidities such as diabetes, hypertension, or dyslipidemia. Conclusions: The H. pylori eradication rate with dual therapy was superior to standard triple therapy. The proton pump inhibitor with the highest eradication rate was esomeprazole. There were no significant differences in eradication according to sex, age, or comorbidities.